Camera-trap records of fishing cat (Prionailurus viverrinus) from East Medinipur (West Bengal, India), and notes on threats to this population. Issue 3 (2nd July 2020) - Chakraborty, Samrat; Barik, Souvik; Saha, Ranjana; Dey, Ajanta; Deuti, Kaushik; Venkatraman, C.; Mazumdar, Subhendu; Saha, Goutam Kumar
ABSTRACT: The fishing cat ( Prionailurus viverrinus ) is a medium-sized felid, which uses various habitats including areas adjoining wetlands. This species is listed as 'vulnerable' in the IUCN Red List 2016, Appendix 2 of CITES and under Schedule 1 of the Wildlife (Protection) Act. In spite of being mired with several threats, studies on fishing cats outside protected areas are scarce in West Bengal, and their confirmed presence has so far been reported only from the Howrah and Hooghly districts. This is the first published account of the presence of fishing cats in human-dominated landscapes of East Medinipur (West Bengal, India) through camera-trap evidence. We have observed that habitat alterations and disturbances associated with the construction of a brick kiln have possibly led to the displacement of fishing cats and other associated wildlife species from the study area. Similar surveys in yet unexplored areas of fishing cat distribution range are needed to identify remaining populations, threats to their survival and to initiate appropriate conservation initiatives. Our findings indicate that current anthropocentric land-use policies need to be reviewed to reduce anthropogenic disturbances and destruction of habitats sustaining fishing cats and other wildlife in human-dominated landscapes.